1991
DOI: 10.1007/bf00155485
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for large scale inoculum development for solid state fermentation system: Conidiospores of Trichoderma harzianum

Abstract: The suitabllity 01 disc fermenter for efficient production of conidiospores by Trichoderma harzianum is limited to a workmg capacity of 0.6 1 agar medium due to large decrease in spore production per cm* of the culture surface area with further increase m Ihc capacity. In contrast, Zymoris, a large scale solid state fermenter designed at ORSTOM, France and USC of men sohd support for absorbing nutrients offer many advantages for production of conidmsporcs m quantity sufflclem enough to inoculate pilot and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Typically, a reduction in Aw extends the lag phase, decreases the specific growth rate, and results in low amount of biomass produced (Oriol et al, 1988b), as shown in fig.2 The optimum moisture content for growth and substrate utilisation is between 40 and 70% but depends upon the organism and the substrate used for cultivation. For example, cultivation of Aspergillus niger on starchy substrates, such as cassava (Raimbault and Alazard, 1980) and wheat bran (Nishio et al, 1979), was optimal at moisture levels considerably lower than on coffee pulp (Penaloza et al, 1991) or sugarcane bagasse (Roussos et al, 1991a(Roussos et al, , 1991b. This is probably because of the greater water holding capacity of the latter substrate (Oriol et al, 1988b).…”
Section: Moisture Content and Water Activity (Aw)mentioning
confidence: 99%
“…Typically, a reduction in Aw extends the lag phase, decreases the specific growth rate, and results in low amount of biomass produced (Oriol et al, 1988b), as shown in fig.2 The optimum moisture content for growth and substrate utilisation is between 40 and 70% but depends upon the organism and the substrate used for cultivation. For example, cultivation of Aspergillus niger on starchy substrates, such as cassava (Raimbault and Alazard, 1980) and wheat bran (Nishio et al, 1979), was optimal at moisture levels considerably lower than on coffee pulp (Penaloza et al, 1991) or sugarcane bagasse (Roussos et al, 1991a(Roussos et al, , 1991b. This is probably because of the greater water holding capacity of the latter substrate (Oriol et al, 1988b).…”
Section: Moisture Content and Water Activity (Aw)mentioning
confidence: 99%
“…Only few data are available regarding spores production, but better yield, morphology, and high stability by means of solid state fermentation have been pointed [33]. In the current work, elevated counts of spores belonging to the two fungal biocontrol agents in the submerged culture were obtained.…”
Section: Discussionmentioning
confidence: 61%
“…For inoculum preparation [17], a PDA medium, with pH adjusted to 6, was prepared and 40 ml placed in Erlenmeyer flasks of 250 ml and autoclaved at 120°, for 20 min. The spores produced on the slant at 30°C for 7 days were collected and inoculated into melted medium cooled to about 45°C.…”
Section: Micro-organism and Inoculum Preparationmentioning
confidence: 99%